2010
DOI: 10.1111/j.1533-2500.2010.00438.x
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Potential CYP450 Pharmacokinetic Drug–Drug Interactions among Osteoarthritis Patients: Incremental Risk of Multiple Prescriptions

Abstract: Abstract:Patients taking more than one drug metabolized through the cytochrome P450 (CYP450) enzyme system experience a drug-drug exposure (DDE), which puts them at risk for a potential pharmacokinetic drug-drug interaction (DDI), defined as two or more drugs interacting in such a way that the effectiveness and/or toxicity of one or all drugs are changed. Any patient subjected to a DDE is at risk for a potentially serious DDI, the epidemiology of which has not been thoroughly studied. Many drugs are metabolize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
25
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 38 publications
5
25
0
Order By: Relevance
“…While the global incidence of PK DDIs is not known, a sharp increase in such DDIs was noted among seniors from 1992 to 2005, with a prevalence of 19.2% in patients 70 years of age 16 . Previous research found a 27% prevalence of DDEs with the potential to cause PK DDIs among ambulatory chronic low back pain patients using CYP450 opioid analgesics 17 and 26% in osteoarthritis 18 .…”
Section: Introductionmentioning
confidence: 99%
“…While the global incidence of PK DDIs is not known, a sharp increase in such DDIs was noted among seniors from 1992 to 2005, with a prevalence of 19.2% in patients 70 years of age 16 . Previous research found a 27% prevalence of DDEs with the potential to cause PK DDIs among ambulatory chronic low back pain patients using CYP450 opioid analgesics 17 and 26% in osteoarthritis 18 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we further improved upon previous work by controlling for exposure to various precipitant/concomitant drugs in the 90-day observation these studies, the exposure of patients with chronic low back pain and osteoarthritis treated with opioids to potential pDDIs was approximately 30%. 16,17 In patients with osteoarthritis taking a CYP450 metabolized opioid, the risk of exposure to a potentially interacting drug was higher in females and increased with age and the number of medications at baseline before receiving an opioid. 18 These data are in agreement with our current results and suggest that many chronic users of opioids are at high risk for potential pDDIs.…”
Section: ■■ Discussionmentioning
confidence: 99%
“…16,17,20,21 These studies comparing costs of exposures, regardless of the clinical importance, could have confounding effects and potentially result in improper estimation of the impact of pDDIs on health care costs. To mitigate this potential, the current study used strict inclusion criteria to focus on patients expected to be most affected by pDDIs (pDDI-Major) as well as obtain patient cohorts that were very similar in terms of baseline characteristics.…”
Section: ■■ Discussionmentioning
confidence: 99%
See 2 more Smart Citations